Comprehensive Evaluation of Rock Mechanical Properties and in-situ Stress in Tight Sandstone Oil Reservoirs - Cai, Mingliyang; Li, Ming; Zhu, Xiaoshuan; Luo, Hao; Zhang, Qiang (Frontiers in Earth Science, 2022)
Comprehensive research on reservoir rock mechanics and in-situ stress properties combined with petrophysical experiments, logging models and numerical simulation is an important means to achieve efficient development of tight sandstone oil reservoirs. In this study, a large number of rock mechanics and acoustic experiments, full-wave train array acoustic wave tests, hydraulic fracturing data and three-dimensional finite element simulations were used to systematically study the rock mechanical properties and in-situ stress characteristics of continental tight oil. Under uniaxial conditions, the tight sandstone samples mainly suffer from discrete tensional ruptures. With the increase of confining pressure, the tight sandstone samples undergo obvious shear ruptures. When the confining pressure is loaded to 35 MPa, a vertical shear fracture is formed. The hydraulic fracturing calculation results show that the in-situ stress state of the target layer satisfies σv>σH>σh. Based on the results of rock mechanics and acoustic tests, we have constructed the dynamic and static mechanical parameter conversion models of tight oil reservoirs and the logging interpretation model of current in-situ stress. Furthermore, the finite element method is used to simulate the three-dimensional structural stress field of the target layer. The simulation results show that the horizontal principal stress distribution in the work area is consistent with the applied environmental stress. The σH of the target layer is mainly distributed in 32~50 MPa, and the σh is mainly distributed in 20~34 MPa. Both σH and σh are relatively high in the southern uplift of the work area; among them, σH is usually greater than 44 MPa, and σh is usually greater than 24 MPa. The northern part of the study area developed several grooves with relatively low stress values. The regions with high stress values are often distributed in bands, which may be related to the compression caused by the deformation of the formation. For shear stress, left-handed and right-handed regions usually alternate with each other. However, the extent of the left-handed area in the southern uplift area is larger than that of the right-handed area, indicating that the tight oil reservoirs in the study area are mainly affected by left-handed activities.